Special plan of management and protection: sustainability tool for tourism in cartagena de indias and its integration with latin america and the caribbean (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2017)
From a critical analysis it was studied the relationship between the PEMP and the tourism sustainability of Cartagena de Indias, being this document a tool of administration and management required to ensure development, joining efforts with a global vision for Latin America and the Caribbean, a study carried out through the Participation in different events organized from governmental estates, forming working tables, constructive dialogues and focus groups, formed by interdisciplinary groups, from all strata and professions, giving a holistic vision to the construction and validation of information.The research evidenced the high degree of interference that the PEM has in the Historic Center of Cartagena de India’s certification, given its high degree of effectiveness as an development generator instrument, synchronizing the lines that include both processes to motivate their interest and commitment to a responsible and rallied job from the different interest groups, for the conservation and preservation of cultural heritage and local sustainability. Therefore, the document is expected to broadly support the different lines exposed for the achievement of such results. The variables that intervene in sustainability were also identified, from different requirements including territorial development: social cohesion, public space, urban complexity; Social variables: poverty, education and security; Economic: employment and income levels; Cultural: tangible and intangible cultural heritage and environmental. As a result, the PEMP ensures management, synergy and local integration, which may well channel twinning that resolve common problems, such as strategies for boosting and sustaining Latin America and the Caribbean
Keywords: tourism development; heritage; sustainability; promotion sectoral technical standards